Державна політика України щодо протидії політичній корупції - Литвин Вікторія Сергіївна (My University, 2023)
У магістерській роботі здійснено аналіз теоретичних аспектів державної політики України щодо протидії політичній корупції та розроблено рекомендації органам публічної влади щодо покращення ефективності політики у цій сфері. В кваліфікаційній роботі розглянуто різні підходи до визначення та класифікації політичної корупції та виявлено ключові проблеми, що потребують подальшого теоретичного та прикладного розв’язання. Досліджено діяльність українських органів влади в сфері боротьби з політичною корупцією. Проаналізовано ефективність механізмів державної політики у сфері протидії політичній корупції. Визначено напрями удосконалення механізмів державної політики у сфері боротьби з політичною корупцією.

Qualifying master's thesis for obtaining a degree of higher education of the second (master's) level in the field of knowledge 28 "Public management and administration", specialty 281 "Public management and administration". –Educational and Scientific Institute of Public Administration and Civil Service of Taras Shevchenko Kyiv National University, Kyiv, 2023. The master's work analyzed the theoretical aspects of the state policy of Ukraine in combating political corruption and developed recommendations for public authorities to improve the effectiveness of policy in this area. In the qualification work, various approaches to the definition and classification of political corruption were considered and key problems were identified that require further theoretical and applied solutions. The activity of Ukrainian authorities in the field of combating political corruption has been studied. The effectiveness of state policy mechanisms in the field of combating political corruption is analyzed. Areas of improvement of state policy mechanisms in the field of combating political corruption have been identified.
Protection of the rights and freedoms of citizens by local self-government bodies: public-management aspect
Keywords: корупція; політична корупція; державна політика; публічні органи влади; corruption; political corruption; state policy; public authorities